The Role of Water Governance in Post-Conflict Peace-Building and Development: A Case of Timor-Leste - Ryan, Christopher (Curtin University, 2021)
This PhD examines water governance in post-conflict Timor-Leste. The aim is to explore an alternative perspective: non-hierarchical undertaking to water governance that is coordinated between state and non-state actors. The findings demonstrate ways of matching a multi-level of policy coordination to a cross-scale of social processes, which provide access to the decision-making process; and increases governance to adapt to uncertainty through a polycentric governance approach. The methodology remains qualitative in nature. These findings contribute to theory-building.